Organisational culture and leadership competencies in ABSA Business Bank: Enterprise Business, Gauteng - Funani, Simphiwe Vincent (Rhodes University, Faculty of Commerce, Rhodes Business School, 2014)
From Integrative summary: This document consists of three sections namely, an evaluation report (section 1), literature review (section 2), and research methodology (section 3). The evaluation report sets out the terms of reference for the research as well as identifying the objectives of the research. It also contains a summary of the literature review section, as well as a research methodology section summary. The literature review section contains a detailed review of the literature used in this study. This section sets out by reviewing existing literature on the topic of leadership, discussing the key elements of organisational culture and includes a short discussion on the typologies of culture. The Competing Values Framework as an organisational culture typology is discussed in greater detail, since it forms the foundation upon which the measurement and data collection tools for this research are founded. The research methodology section explains the research methodology and design employed in this study. This section also addresses some of the ethical considerations for this research, as well as how the researcher addressed them. There is also a brief discussion on the limitations of the research and the application of the results. This research focused on a business unit within Absa Business Bank, named Enterprise Business Gauteng Region, with the aim of investigating the "current organisational culture" in the business unit and the leadership competencies profile of its 11 Sales Managers. This was to provide the basis and departure point for the strategic organisational culture change that the new business unit head would have wanted to effect as the business has a history of non-performance, which the new business unit head aims to change. In order to diagnose the "current organisational culture" type, an organisational culture measurement tool based on the Competing Values Framework was used. The Competing Values Framework is a four-category organisational culture typology developed by Cameron and Quinn. The framework is based on two dimensions, how stable or flexible the organisation is, and how externally or internally focused it is. This framework was also employed to establish the leadership competencies profile of Sales Managers, as observed and experienced by the frontline staff, as well as the "desired organisational culture" , as intended by the new business unit head. Through hypotheses testing, the research revealed a statistically significant difference in perceptions of culture between males and females in the business unit. The perceptions of the female frontline staff about the "current" business unit culture indicated that they find it not to be empowering and less allowing for individuality and risk taking when compared to the male staff. The research also concluded that there is no statistically significant difference between leadership competencies associated with the four categories of the Competing Values Framework in the business unit. Comparisons between the "current" and the "desired" organisational culture revealed a misalignment. The main recommendations to the new business unit head were to get the leadership competencies of the Sales Managers aligned with the "desired organisational culture" state, and drive a purposive organisational culture change effort. To support this culture change, the espoused values of the business unit would need to be aligned to the desired culture state. To address the differences in perceptions of culture between males and females the business unit head would need to be mindful of the greater need to empower women either in their current roles, or by way of promotions to senior roles.
Keywords: ABSA Bank; Corporate culture; Organizational behavior; Leadership Leadership -- Ability testing; Business enterprises -- Personnel management; Executives -- Training of; Organizational effectiveness